(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2026)
This study aims to determine the efficacy of GrafoSofos in developing writing skills in campus journalism among third-year English majors at Bestlink College of the Philippines. It focuses on respondents’ profiles in terms of age, sex, experience with digital tools, and prior experience in journalism. The utilization of GrafoSofos, an instructional material designed to improve students’ writing proficiency, is examined to assess its effectiveness in enhancing journalistic writing skills. The study utilizes a quasi-experimental design. A total of 50 third-year English major students, composed of 10 males and 40 females, were selected as participants. Pre-tests and post-tests were administered to assess the development of writing skills before and after the use of GrafoSofos. The evaluation concentrated on journalistic style, grammar, punctuation, and vocabulary, with scoring based on a structured rubric. The instructional material served as the main intervention between the assessments. Findings revealed a significant improvement in writing performance after the use of GrafoSofos. The post-test results showed a marked increase in scores, with an overall mean of 4.42, which was verbally interpreted as excellent. These results indicate that the instructional tool effectively enhanced the writing skills of third-year English majors, particularly in terms of journalistic clarity, structure, and language usage. The study concludes that effective written communication is essential for academic and professional success. The integration of GrafoSofos demonstrated positive outcomes in improving coherence, creativity, and clarity in student writing. Its interactive features, immediate feedback mechanisms, and content-focused activities contributed to measurable skill development. Based on the findings, the study recommends incorporating GrafoSofos more broadly into the English curriculum to support writing instruction in campus journalism and enhance digital literacy in academic writing contexts.